Evaluation of The Library and Archives of East Javaâs Workshop as A Knowledge Sharing Form of Jawatimuran Local Wisdom Preservation - Atmi, Ragil Tri (Record and Library Journal, 2015)
Local wisdom possessed by the East Java is a form of culture that represents the identity of the Jawatimuran that does not shared by other regions, but the social dynamics and development of information technology make the knowledge of local wisdom faded and forgotten, so that the next generation remains to know, love and proud in the culture of their own country, then that knowledge must be preserved. The Library and Archives of East Java has organized several workshops. Those workshops are a form of knowledge sharing as an effort to preserve local wisdom of Jawatimuran through writing. The purpose of this study is to evaluate the workshops conducted by The Library and Archives of East Java. The methodology used in this study is a qualitative descriptive method. The results of this study show that knowledge sharing can improve the productivity of the authors and creates integration between authors, publishers and The Library and Archives of East Java in an effort to preserve local wisdom in East Java. The conclusion is that The Library and Archives of East Java should be a bridge for the writers to continue to produce writings based on the local wisdom.